The Effectiveness Test of Tembelekan (Lantana camara L.) Leaf Extract Gel for Cuts Healing in Male White Mice - Khonsa (Media Farmasi Indonesia, 2025)
The study of natural products as an alternative medicine to speed up the cuts healing process has become a popular topic of scientific research. One of the plants is Tembelekan (Lantana camara L.) leaves. Its formulation into a gel form can increase drug release. This study aims to determine the effectiveness of Tembelekan leaf extract gel preparations for healing cut wounds in male white mice. The method used in this research was an experimental method on 5 groups with 5 mice in each group. The positive control group was given Bioplacenton®, the negative control group was given gel base, and the treatment group was given 10%, 15%, and 20% Tembelekan leaf extract gel. The gel was applied to the wound twice a day and the observation used Linkert scale. Based on the results of the Kruskal Wallis test, an Asymp.Sig value of 0,030 < 0,050 was obtained, indicating that Tembelekan leaf extract gel was effective in healing cuts. Tembelekan leaf extract gel with varying concentrations of 10%, 15% and 20% has an effect of healing cuts in male white mice. The fastest healing of cuts occurred within 9 days with Tembelekan leaf extract gel with a concentration of 20%. Keywords: Tembelekan, cuts, wound healing, gel, effectiveness test